The effects of comprehensive income on investors' judgments: An investigation of one-statement vs. two-statement presentation formats. Issue 3 (2nd November 2015) - Du, Ning; Stevens, Kevin; McEnroe, John
Abstract : Purpose: – This paper aims to understand the effects of different presentation formats on nonprofessional investors' judgments. Both International Financial Reporting Standards and US Generally Accepted Accounting Principles require an entity to present items of net income and other comprehensive income (OCI) either in one continuous or in two separate, but consecutive, statements but limited understanding exists about their differential effects on evaluation of company performance. Design/methodology/approach: – To investigate this research question, we used a two (Financial Position) x two (Format) randomized between-subjects experiment. Ninety-four graduate students assumed the role of investor and participated in this study. Findings: – Results of the experiment suggest that participants are more likely to incorporate OCI information presented in the one-statement format than in the two-statement format. Further analysis suggests that participants both assign more weight to OCI and perceive OCI to be relatively more important in the one-statement format than in the two-statement format, especially when the entity suffers an economic loss. Originality/value: – Results from this study provide evidence to the Financial Accounting Standards Board and International Accounting Standards Board that should be useful in evaluating the effectiveness of alternative comprehensive income reporting formats and should be of interest to accounting rule-making bodies, investors, publicly traded entities and financial analysts, among others.